Pengembangan E- Modul Interaktif Berbasis Canva Dengan Pendekatan PMRI Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa - Ningrum, Putri Aditia; Rohim, Abdur (WAHANA PEDAGOGIKA: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
The aim of this research is to develop teaching materials in the form of Canva-based mathematics e-modules with the PMRI approach to statistics material. The research carried out by the author is research and development (Research & Development) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The instruments used in this research include expert validation questionnaires, student response questionnaires, teacher practicality questionnaires and tests of students' problem solving abilities. The presentation of material in the e-module is prepared based on the principles of the PMRI approach with the test subjects being class VIII students at Al Ma'ruf Turi Middle School. Based on the validation results, it was found that the e-module met the valid criteria without revision and met the overall percentage of media experts at 91.6% and material experts at 90%, so the e-module was suitable for testing. After being tested, the practicality criteria were obtained with a percentage of 90.1%, which shows that the criteria are very practical. Furthermore, the student test results in the problem solving ability test showed that a percentage of 80% of students achieved classical completeness. Based on these data, it can be concluded that the E-Module has met the valid criteria without revision, is very practical and effective for use in the mathematics learning process for class VIII students.